A single stage posterior approach and rigid fixation for preventing kyphosis in the treatment of spinal tuberculosis - (:unkn) unknown (My University, 1994)
Study Design. The authors employed a new mode of treatment for spinal tuberculosis consisting of single stage posterior instrumentation and fusion without anterior debridement. Ten patients were operated uponi n this manner. Chemotherapy was instituted 2 weeks pre-operatively and continued for a mean period of 11 months. Cotrel-Dubousset or a comparable system was used for fixation. Objectives. Patients were followed for 3 monthly intervals with serial anteropostorior and lateral x-rays, erythrocyte sedimentation rate, physical examination, and patients self reports. The mean follow up period was 24.2 months (range, 17-36 months). Methods. Measurement of kyphosis angle in the lateral x-ray view was used to evaluate treatment. Results. Only a 3.4° mean loss of correction was abserved over the follow-up period. All patiants were satisfied. Conclusion. Our results show that posterior rigid fixation and chemotherapy provide satisfactory stabilization, reduce sufigical morbidity, and prevent development of late kyphosia in selected patients with Pott’s disease of the thoracolumbar spine. © 1994, J.B. Lippincott Company.
Keywords: Posterior instrumentation; Spinal tuberculosis